The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1039/c9dt02420d
|View full text |Cite
|
Sign up to set email alerts
|

Mo-Based crystal POMOFs with a high electrochemical capacitor performance

Abstract: The capacitor performance of newly synthesized crystalline POMOFs was higher than those of the majority of reported POMOF-, state-of-the-art MOF- and POM-based materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 64 publications
1
41
0
Order By: Relevance
“…In sharp contrast to the inorganic electrode materials, their diverse topology structure, tunable porosity, and abundant metal ions allow them to be a promising energy storage material . However, the poor conductivity and lack of structural stability of pristine MOFs remain the critical limitations for practical applications in energy storage devices . Except for MOFs‐derived nanocarbons or metal compounds, hybridizing MOFs with conductive polymers or carbon substrates is an additional productive tactic to improve the conductivity and stability, which can accelerate the electron transfer and reduce the inner resistance during the electrochemical reactions, even though the loading of active MOF species is lowered by the existence of conducting materials in a hybrid composition .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In sharp contrast to the inorganic electrode materials, their diverse topology structure, tunable porosity, and abundant metal ions allow them to be a promising energy storage material . However, the poor conductivity and lack of structural stability of pristine MOFs remain the critical limitations for practical applications in energy storage devices . Except for MOFs‐derived nanocarbons or metal compounds, hybridizing MOFs with conductive polymers or carbon substrates is an additional productive tactic to improve the conductivity and stability, which can accelerate the electron transfer and reduce the inner resistance during the electrochemical reactions, even though the loading of active MOF species is lowered by the existence of conducting materials in a hybrid composition .…”
mentioning
confidence: 99%
“…The Co‐Ni‐B‐S presents the highest capacitance with two pairs of redox peaks at the scan rate of 20 mV s −1 , whereas only one pair for the other materials (Co‐Ni MOF, Co‐Ni‐B, Co‐Ni‐S, and Co‐Ni‐S‐B) is resulted from the Co/Ni multivalences and amorphous structure after the redox treatment . The electrochemically active surface area (ECSA) of Co‐Ni MOF and its derivatives are also evaluated through the CV measurements at the potential window (0–0.1 V versus Hg/HgO) (Figure S10, Supporting Information) . The specific electrical double layer capacitance ( C dl ) of Co‐Ni MOF, Co‐Ni‐B, Co‐Ni‐B‐S, Co‐Ni‐S, and Co‐Ni‐S‐B is 110.66, 45.8, 145.4, 48, and 2.5 F g −1 , respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…reported that the NENU‐5/PPy nanocomposite has 5147 mF cm −2 and a symmetric supercapacitor device was developed in 2018. In 2019, Li et al . studied Mo‐based POMOFs, the highest specific capacitance of which was 249.0 F g −1 .…”
Section: Introductionmentioning
confidence: 99%
“…[31] reported that the NENU-5/PPy nanocomposite has5 147 mF cm À2 and as ymmetric supercapacitor device was developed in 2018. In 2019, Li et al [32] studied Mo-based POMOFs, the highest specific capacitance of which was 249.0 Fg À1 .I nP OMOFs, the silver ion with d 10 configuration is as oft Lewis acid metal ion, and the multifunctional coordination number and the adjustable coordination shell can be adopted to increase the chance of coordination with the POMs andt he organic ligands. Meanwhile, Ag-MOF and Ag-POMOFs [33,34] have been little researched for SCs, mainly because these substances are synthesized by hydrothermal methods, which have the disadvantages of tedious experiments, long reaction times, low yields, and poor stability of repeated synthesis.…”
Section: Introductionmentioning
confidence: 99%